Provably Secure Client-Server Key Management Scheme in 5G Networks. (22nd October 2021) - Yang, Lei; Chen, Yeh-Cheng; Wu, Tsu-Yang
Abstract : The increasing demand for real-time data transmission in wireless mobile communication networks has promoted the maturity of mobile communication technology. Fifth-generation (5G) mobile communication technology is combined with cloud computing, high-frequency signal transmission, and other technologies and perfectly fits with the client-server architecture. 5G has been applied in many fields, such as the interconnection of smart devices, virtual reality, and cloud-based life. To provide the security and availability of the required services, we proposed a key management scheme based on the multiserver architecture of the client-server mode in 5G networks, which uses bilinear pairings and elliptic curve cryptography. Through informal security analysis and formal analysis (under the random oracle model and ProVerif tool), we demonstrated that the proposed scheme can complete mutual authentication and resist common network attacks. Furthermore, after the performance analysis of our scheme and other related schemes, it was found that this scheme has relatively low communication and computation costs and better security performance.